Resuscitation of functional bacterial community for enhancing biodegradation of phenol under high salinity conditions based on Rpf. (August 2018) - Su, Xiaomei; Wang, Yuyang; Xue, Binbing; Zhang, Yunge; Mei, Rongwu; Zhang, Yu; Hashmi, Muhammad Zaffar; Lin, Hongjun; Chen, Jianrong; Sun, Faqian
Graphical abstract: Highlights: Rpf accelerated the start-up process during sludge domestication. Rpf enhanced salt-tolerant phenol-degrading capability of functional bacteria. Functional bacteria in response to Rpf belonged to Actinobacteria and Bacteroidete . Rpf is a promising additive for enhancing saline phenolic wastewater treatment. Abstract: This study assumed that key degraders of functional bacterial community were prone to enter into the viable but non-culturable (VBNC) state under high saline phenolic conditions, and resuscitation-promoting factor (Rpf) could strengthen these degraders for better performances. Based on these assumptions, Rpf was used to enhance salt-tolerant phenol-degrading capability of functional populations in activated sludge. Results suggested that Rpf accelerated the start-up process during sludge domestication, and significantly enhanced salt-tolerant phenol-degrading capability. High-throughput sequencing showed that the resuscitation and stimulation functions of Rpf linked mainly to the genus Corynebacterium within the phylum Actinobacteria, and the genera Proteiniphilum and Petrimonas within the phylum Bacteroidete . These key functional populations contributed to better phenol-degrading capabilities under high salinity conditions. This study indicated that Rpf is a promising additive for improving biological treatment performance of saline phenolic wastewater.